Regulators as 'agents': power and personality in risk regulation and a role for agent-based simulation - Davies, Gareth J.; Kendall, Graham; Soane, Emma; Li, Jin; Charnley, Fiona; Pollard, Simon J. T. (Taylor & Francis, 2010)
We critically examine how evidence and knowledge are brokered between the various actors (agents) in regulatory decisions on risk. Following a precis of context and regulatory process, we explore the role power and personality might play as evidence is synthesised and used to inform risk decisions, providing a review of the relevant literature from applied psychology, agent-based simulation and regulatory science. We make a case for the adoption of agent- based tools for addressing the sufficiency of evidence and resolving uncertainty in regulatory decisions. Referring to other environmental applications of agent- based decision-making, we propose how an agent model might represent power structures and personality characteristics with the attending implications for the brokering of regulatory science. This critical review has implications for the structuring of evidence that informs environmental decisions and the personal traits required of modern regulators operating in facilitative regulatory settings.
Keywords: agent-based simulation personality power risk regulation situation interaction interpersonal-trust perceived trustworthiness moderating impact decision-making 5-factor model blood-pressure social power weak ties knowledge